2001
DOI: 10.1161/01.hyp.37.3.827
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N-Acetyl-Seryl-Aspartyl-Lysyl-Proline on DNA and Collagen Synthesis in Rat Cardiac Fibroblasts

Abstract: N-Acetyl-seryl-aspartyl-lysyl-proline (Ac-SDKP) is a natural inhibitor of pluripotent hematopoietic stem cell entry into the S phase of the cell cycle and is normally present in human plasma. Ac-SDKP is exclusively hydrolyzed by ACE, and its plasma concentration is increased 5-fold after ACE inhibition in humans. We examined the effect of 0.05 to 100 nmol/L Ac-SDKP on 24-hour 3 H-thymidine incorporation (DNA synthesis) by cardiac fibroblasts both in the absence and presence of 5% FCS. Captopril (1 mol/L) was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
114
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(124 citation statements)
references
References 56 publications
(49 reference statements)
10
114
0
Order By: Relevance
“…In addition, the order of combination did not make any difference in either the BPlowering or the anti-albuminuric effect. The mechanisms responsible for the excellent effects of the combinations may involve more complete blockade of RAS, activation of angiotensin type 2 receptors, and/or increased levels of bradykinins and N-acetyl-seryl-aspartyl-lysyl-proline (Ac-SDKP) (24)(25)(26)(27)(28). We have recently shown that in patients with diabetic nephropathy, addition of an ARB to an ACEI reduced both BP and ACR, and the reduction of ACR was closely associated with the reduction of urinary markers of oxidative stress (29).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the order of combination did not make any difference in either the BPlowering or the anti-albuminuric effect. The mechanisms responsible for the excellent effects of the combinations may involve more complete blockade of RAS, activation of angiotensin type 2 receptors, and/or increased levels of bradykinins and N-acetyl-seryl-aspartyl-lysyl-proline (Ac-SDKP) (24)(25)(26)(27)(28). We have recently shown that in patients with diabetic nephropathy, addition of an ARB to an ACEI reduced both BP and ACR, and the reduction of ACR was closely associated with the reduction of urinary markers of oxidative stress (29).…”
Section: Discussionmentioning
confidence: 99%
“…This protects high-affinity receptors, blocks receptor desensitization and decreases internalization, thereby potentiating BK beyond blocking its hydrolysis. 156,157 ACEis also directly activate the bradykinin B 1 receptor by acting at the zinc-binding pentameric consensus sequence HEXXH (195)(196)(197)(198)(199) of the B 1 receptor, a motif that is present in the active center of ACE but absent from the B 2 receptor. ACEis, when activating the B1 receptor, elevate intracellular calcium ([Ca 2+ ]i) and release NO from cultured cells.…”
Section: Looking Beyond Ace Inhibitionmentioning
confidence: 99%
“…196 AcSDKP has antiproliferative and antifibrotic activities, and it protects hematopoietic stem cells against chemotherapy-induced injury 196 and limits cardiac fibrosis. 197 The current-generation ACEis in clinical use are essentially mixed N-and C-domain inhibitors. 198 Captopril has been noted to be modestly N-selective depending on Cl À concentration, whereas lisinopril and enalaprilat are more C-selective 194,199 (Figure 3).…”
Section: Future Of Aceismentioning
confidence: 99%
“…The plasma levels of Ac-SDKP were shown to be increased by fivefold after the administration of ACE-I in humans (13). Ac-SDKP was shown to suppress the proliferation of renal fibroblasts (14) and to inhibit DNA synthesis as well as collagen deposition in cardiac fibroblasts (15). In a hypertensive rat model, long-term administration of Ac-SDKP can ameliorate renal fibrosis and ventricular hypertrophy (16,17).…”
mentioning
confidence: 99%